2022
DOI: 10.1097/md.0000000000030047
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the clinical practice followed by Korean medicine doctors for scoliosis: Preliminary data for clinical practice guidelines

Abstract: Scoliosis is a spinal disease in which the Cobb angle is >10°. Scoliosis treatment can be surgical or conservative, and clinical practice guidelines (CPGs) for conservative treatments have been updated since 2006. There have been several articles regarding the efficacy and safety of Korean medicine (KM) in treating scoliosis, but there are no CPGs. Our study investigated the current clinical practice using a survey for the future establishment of KM-CPGs. The survey mainly comprised clinical practice status, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…His early study on pharmacopuncture prospectively observed the long-term effects of integrative therapy, including pharmacopuncture in lumbar disc herniation [ 33 ]. His recent studies included a survey to develop a KM CPG for scoliosis [ 34 ] and a pragmatic randomized controlled trial protocol to investigate the effectiveness and safety of pharmacopuncture for chronic lower back pain [ 35 ]. These clusters were dense and overlapping, but Kyeong Han Kim and Soo-Hyun Sung were located laterally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…His early study on pharmacopuncture prospectively observed the long-term effects of integrative therapy, including pharmacopuncture in lumbar disc herniation [ 33 ]. His recent studies included a survey to develop a KM CPG for scoliosis [ 34 ] and a pragmatic randomized controlled trial protocol to investigate the effectiveness and safety of pharmacopuncture for chronic lower back pain [ 35 ]. These clusters were dense and overlapping, but Kyeong Han Kim and Soo-Hyun Sung were located laterally.…”
Section: Resultsmentioning
confidence: 99%
“…Over time, studies on pharmacopuncture have increased the level of evidence in the context of EBM. For example, recent surveys of KMDs [ 17 , 34 ] examining the use of pharmacopuncture in the context of KM CPG development, randomized controlled trials [ 3 , 4 , 22 , 35 ] using pharmacopuncture, and a meta-analysis [ 1 ] have been conducted. These results can be interpreted as the quantitative and qualitative growth of pharmacopuncture studies in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…On the topic of the NLE-KMD, to our knowledge, our study is the latest to investigate and analyze the current perceptions of KMDs and the first to gather more than 1000 KMD opinions. Because of our survey’s significant number of respondents, our study potentially provides a more representative justification than previous surveys in which KMDs participated [ 40 ]. However, there are some limitations.…”
Section: Discussionmentioning
confidence: 99%